1978
DOI: 10.1002/crat.19780131110
|View full text |Cite
|
Sign up to set email alerts
|

Impurity diffusion of 114In in Cu

Abstract: Using the tracer-standard sectioning technique the impurity diffusion of indium in copper has been investigated in the temperature range from 798.1 to 1081.0 "C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The subscript Culn 2 , indicating the stoichiometry of this phase, will be justified later. No fraction for in In in Cu with Vzz = 0 caused by the cubic crystal structure is detected, which excludes In diffusion in Cu in our annealing temperature range, as expected from known diffusion data 5. Figure 2summarizes the isochronal annealing experiments, showing the dependence of the fraction /cuin 2 (left scale) for the new phase as a function of annealing temperature.…”
supporting
confidence: 57%
“…The subscript Culn 2 , indicating the stoichiometry of this phase, will be justified later. No fraction for in In in Cu with Vzz = 0 caused by the cubic crystal structure is detected, which excludes In diffusion in Cu in our annealing temperature range, as expected from known diffusion data 5. Figure 2summarizes the isochronal annealing experiments, showing the dependence of the fraction /cuin 2 (left scale) for the new phase as a function of annealing temperature.…”
supporting
confidence: 57%
“…In comparison of the bulk diffusion parameters ( D 0 and Q ) of In segregation obtained from this study and those obtained from literature for In impurity diffusion in Cu crystals investigated using the tracer method, Table was completed and the Arrhenius graphs were plotted for In diffusion in Cu crystals (see Figure ). The Arrhenius lines in Figure are very close, which shows a good comparison between the bulk diffusion parameters of In segregation obtained in this study and those found in literature.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the attractive interaction between the In and Cu atoms, a strong attractive interaction between the S and Cu atoms (Ω CuÀS = 23.0 kJ.mol À1 ) set a preference for unlike first-neighbour bonds formation between the S and Cu atoms and propose that an S atom occupies the Cu surface substitutionally and prefers to bond with Cu atoms. In comparison of the bulk diffusion parameters (D 0 and Q) of In segregation obtained from this study and those obtained from literature for In impurity diffusion in Cu crystals investigated using the tracer method, [9][10][11] Table 2 was completed and the Arrhenius graphs were plotted for In diffusion in Cu crystals (see Figure 6). The Arrhenius lines in Figure 6 are very close, which shows a good comparison between the bulk diffusion parameters of In segregation obtained in this study and those found in literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations